Trends in 28-Day Mortality of Critical Care Patients With Coronavirus Disease 2019 in the United Kingdom: A National Cohort Study, March 2020 to January 2021*. Issue 11 (13th July 2021) - Dennis, John M.; McGovern, Andrew P.; Thomas, Nicholas J.; Wilde, Harrison; Vollmer, Sebastian J.; Mateen, Bilal A.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To determine whether the previously described trend of improving mortality in people with coronavirus disease 2019 in critical care during the first wave was maintained, plateaued, or reversed during the second wave in United Kingdom, when B117 became the dominant strain. DESIGN: National retrospective cohort study. SETTING: All English hospital trusts (i.e., groups of hospitals functioning as single operational units), reporting critical care admissions (high dependency unit and ICU) to the Coronavirus Disease 2019 Hospitalization in England Surveillance System. PATIENTS: A total of 49, 862 (34, 336 high dependency unit and 15, 526 ICU) patients admitted between March 1, 2020, and January 31, 2021 (inclusive). INTERVENTIONS: Not applicable. MEASUREMENTS AND MAIN RESULTS: The primary outcome was inhospital 28-day mortality by calendar month of admission, from March 2020 to January 2021. Unadjusted mortality was estimated, and Cox proportional hazard models were used to estimate adjusted mortality, controlling for age, sex, ethnicity, major comorbidities, social deprivation, geographic location, and operational strain (using bed occupancy as a proxy). Mortality fell to trough levels in June 2020 (ICU: 22.5% [95% CI, 18.2–27.4], high dependency unit: 8.0% [95% CI, 6.4–9.6]) but then subsequently increased up to January 2021: (ICU: 30.6% [95% CI, 29.0–32.2] and high dependency unit, 16.2% [95% CI, 15.3–17.1]). Comparing patients admitted during June–September 2020 with those admitted during December 2020–January 2021, the adjusted mortality was 59% (CI range, 39–82) higher in high dependency unit and 88% (CI range, 62–118) higher in ICU for the later period. This increased mortality was seen in all subgroups including those under 65. CONCLUSIONS: There was a marked deterioration in outcomes for patients admitted to critical care at the peak of the second wave of coronavirus disease 2019 in United Kingdom (December 2020–January 2021), compared with the post-first-wave period (June 2020–September 2020). The deterioration was independent of recorded patient characteristics and occupancy levels. Further research is required to determine to what extent this deterioration reflects the impact of the B117 variant of concern.